Funding emergency care: Australian style. (13th July 2014) - Bell, Anthony; Crilly, Julia; Williams, Ged; Wylie, Kate; Toloo, Ghasem (Sam); Burke, John; FitzGerald, Gerry
Abstract The ongoing challenge for ED leaders is to remain abreast of system‐wide changes that impact on the day‐to‐day management of their departments. Changes to the funding model creates another layer of complexity and this introductory paper serves as the beginning of a discussion about the way in which EDs are funded and how this can and will impact on business decisions, models of care and resource allocation within Australian EDs. Furthermore it is evident that any funding model today will mature and change with time, and moves are afoot to refine and contextualise ED funding over the medium term. This perspective seeks to provide a basis of understanding for our current and future funding arrangements in Australian EDs.